The adaptive threat bias in anxiety: Amygdala–dorsomedial prefrontal cortex coupling and aversive amplification - Robinson, Oliver J.; Charney, Danielle R.; Overstreet, Cassie; Vytal, Katherine; Grillon, Christian (NeuroImage (Orlando, Fla.), 2012)
Functionally, anxiety serves to increase vigilance towards aversive stimuli and improve the ability to detect and avoid danger. We have recently shown, for instance, that anxiety increases the ability to a) detect and b) instigate defensive responses towards aversive and not appetitive face stimuli in healthy individuals. This is arguably the key adaptive function of anxiety, yet the neural circuitry underlying this valence-specific effect is unknown. In the present translational study, we sought evidence for the proposition that dorsomedial regions of the prefrontal (DMPFC) and cingulate cortex constitute the human homologue of the rodent prelimbic and are thus associated with increased amygdala responding during this adaptive threat bias in anxiety. To this end, we applied a novel functional connectivity analysis to healthy subjects (N=20) identifying the emotion of fearful and happy faces in an fMRI scanner under anxious (threat of unpredictable foot shock) and non-anxious (safe) conditions. We showed that anxiety significantly increased positive DMPFC–amygdala connectivity during the processing of fearful faces. This effect was a) valence-specific (it was not seen for happy faces), b) paralleled by faster behavioral response to fearful faces, and c) correlated positively with trait anxiety. As such we provide the first experimental support for an anxiety-mediated, valence-specific, DMPFC–amygdala aversive amplification mechanism in healthy humans. This may be homologous to the rodent prelimbic–amygdala circuit and may, given the relationship with trait anxiety, underlie vulnerability to anxiety disorders. This study thus pinpoints a key neural mechanism in adaptive anxiety and highlights its potential link to maladaptive anxiety. ► Anxiety adaptively increases vigilance to aversive stimuli. ► We used fMRI to examine emotional face processing during induced anxiety. ► Increased DMPFC–amygdala coupling was associated with increased aversive vigilance. ► Correlates with trait anxiety and may thus drive anxiety disorder vulnerability. ► May be the human homologue of the rodent prelimbic–amygdala circuit.